Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Explorations in contemporary feminist literature: The battle against oppression for writers of color, lesbian and transgender communities - Pernal, Mary (P. Lang, 2002)
Explorations in Contemporary Feminist The Battle Against Oppression for Writers of Color, Lesbian and Transgender Communities is a work that bridges issues of oppression across diverse communities within the contemporary feminist movement. Fictional writings by authors such as Toni Morrison, Maya Angelou, Rose Tremain, and others are addressed in regard to their content of social messages. The major focus of this book is the need for personal-redefinition by members of marginalized communities seeking a ground of self-determination and respect, as expressed by various authors. The connections between authors' perspectives are rasied and a critical gaze is directed at the claim that personal choice equates with freedom.
Keywords: afro-féminisme; amériques; approches et analyses; arts; classisme; discipline; intersectionnalité; littérature; personnes lesbiennes; personnes trans*; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires

Garçon manqué - Bouraoui, Nina (Librairie générale française, 2000)
Dans les années 70, la guerre d'Algérie est encore dans tous les esprits. Ce récit autobiographique décrit la difficulté de vivre en Algérie avec une mère française, et de vivre en France avec un père algérien
Section: 188 pages ; 18 cm
Keywords: 1900-1999; 1970-1979; afrique; afrique du nord; algérie; approches et analyses; arts; cours; discipline; europe; france; lit2815; premier cycle; périodes historiques; racisme; roman; régions géographiques; système colonial; systèmes d'oppressions; études littéraires